2021
DOI: 10.1042/bcj20200754
|View full text |Cite|
|
Sign up to set email alerts
|

Rivastigmine attenuates the Alzheimer's disease related protein degradation and apoptotic neuronal death signalling

Abstract: Rivastigmine is clinical drug for patients of Alzheimer’s disease (AD) exerting its inhibitory effect on acetylcholinesterase activity however, its effect on other disease related pathological mechanisms are not yet known. This study was conducted to evaluate the effect of rivastigmine on protein aggregation and degradation related mechanisms employing streptozotocin (STZ) induced experimental rat model. The known inhibitory effect of rivastigmine on cognition and acetylcholinesterase activity was observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…PCNA, proliferating cell nuclear antigen. et al [49] confirmed the present results as they found that RIVA has a significant ameliorative effect on AD's related biochemical alterations, protein degradation machinery, and neuronal apoptosis through the inhibitory effect of RIVA on AChE activity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…PCNA, proliferating cell nuclear antigen. et al [49] confirmed the present results as they found that RIVA has a significant ameliorative effect on AD's related biochemical alterations, protein degradation machinery, and neuronal apoptosis through the inhibitory effect of RIVA on AChE activity.…”
Section: Discussionsupporting
confidence: 88%
“…[ 8,38 ] RIVA decreased oxidative stress and apoptosis. [ 11,49 ] Therefore, RIVA increased the HO‐1 level. This may explain the increase in gastric HO‐1 levels in RIVA‐treated rats as observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental rats were anesthetized using a mixture of xylazine (10 mg/kg) and ketamine (80 mg/kg), mounted on the stereotaxic apparatus (Stoelting, USA) and a specific region was located by measuring coordinates from bregma(Anon n.d.). Unilateral administration (on the right side of rat brain) of rotenone (dissolved in 3μl DMSO, 6μg in each region) was given in the substantia nigra (SN) and striatum (STR) region (Gupta, et al 2021). Appropriate care of rats was taken to prevent mortality and after completion of experimental duration (3 days post administration) the rats were sacrificed, both SN and STR were isolated and processed for various assays or the brains were fixed for histological or immunofluorescence studies.…”
Section: Methodsmentioning
confidence: 99%
“…Proteasome activity was estimated in both cell (WT and Myc-UBA52) and tissue lysates as reported by us previously (Gupta, Tiwari, et al 2021) utilizing trypsin (Z-ARR-AMC) and chymotrypsin (SUC-LLVY-AMC) substrate (Enzo life sciences). Reaction mixtures were incubated for 60 minutes at 37 °C in dark and the fluorescence intensity was measured using fluorimeter (Varian Cary Eclipse, USA) at excitation/emission 360/460nm, respectively.…”
Section: Proteasome Activitymentioning
confidence: 99%
“…Three transmembrane ER sensors, including activating transcription factor 6 (ATF6), protein kinase R-(PKR-) like endoplasmic reticulum kinase (PERK), and inositol-requiring enzyme 1 (IRE1α), have been found to determine the triggering of ER stress and subsequent activation of the UPR [7]. With the increasing recognition of ER stress mechanisms, ER stress dysregulation has been found to play an essential role in various human diseases, including cardiometabolic diseases [8][9][10], diabetes [11,12], chronic kidney disease [13,14], Alzheimer's disease [15,16], and cancers [17][18][19][20]. Chronic activation of the UPR caused by ER stress, viral infection, or hepatic obesity may lead to liver dysfunction and disturbances in lipid and glucose metabolism [21].…”
Section: Introductionmentioning
confidence: 99%